Doing probes diary with children in reporting social networking behaviour - Azmi, Noor Hidayah; Abdul Razak, Fariza Hanis (2015)
This paper describes the qualitative technique approach in an attempt to understand child personality with regards to social networking sites.It was applied during the user requirement phase.We used a probes diary approach to collect qualitative data from selected children.Seven children from 10-13 years old participated in the study and completed the diary.In this paper, we describe about our probes diary approach with young children participants.We have identified seven important elements in designing diaries for children. We believe that the work presented in this paper might help other researchers to design children's diary for their own research.